Repeated Sprint Ability and Muscular Responses According to the Age Category in Elite Youth Soccer Players - Sánchez-Sánchez, Javier; García-Unanue, Jorge; Hernando, Enrique; López-Fernández, Jorge; Colino, Enrique; León-Jiménez, Manuel; Gallardo, Leonor (Frontiers in Physiology, 2019)
The aim of this study was to analyse the influence of age category on the performance and muscle response after a Repeated Sprint Ability (RSA) test in elite youth soccer players. 62 soccer players from three different age categories (Under 14 [n=21], Under 16 [n=20] and Under 18 [n=21]) were selected to participate in this study. Players completed an RSA test (7 x 30 m) with a 20-second recovery between sprints. The muscular response to an electrical stimulus before and after the test of both the biceps femoris (BF) and the rectus femoris (RF) were evaluated using tensiomyography. A two-way ANOVA was used to analyse the differences in RSA parameters in each of the four distance-intervals (0-5; 5-25; 25-30; 0-30 m) between sprint and age category. The U14 age category (5.30 ± 0.30 s) showed higher mean sprint times than U16 (4.62 ± 0.20 s) and U18 (4.46 ± 0.17s) throughout the entire test (p<0.01). U16 players revealed a worse best sprints time (RSABEST) than U18 players (+0.12 s, CI95%: to 0.01 to 0.24; ES: 1.09, p = 0.03). The muscular contractile properties were similar in the three age categories analysed (p>0.05), although the delay time (Td) of the muscle was significantly lower after the RSA test in U16 players (-1.53 ms, CI95%: -2.607 to -0.452; ES: 0.38) and U18 players (-1.11 ms, CI95%: - 2.10 to - 0.12; ES: 0.22). In conclusion, this study revealed an increase in physical performance and muscle response variability after a repeated sprint ability test in the U16´s and over. The fatigue induced by the RSA test did not show differences depending on the age of the players, although muscle mechanical properties were altered after the RSA test in U16 and U18 soccer players. Physical performance and muscle response can be complementary variables in managing fatigue according to the age category in soccer players.